2013
DOI: 10.1029/2012jb009527
|View full text |Cite
|
Sign up to set email alerts
|

An integration to optimally constrain the thermal structure of oceanic lithosphere

Abstract: [1] The evolution through time of the oceanic lithosphere is a substantial, incompletely resolved geodynamical problem. Consensus remains elusive regarding its thermal structure, physical properties, and the best model through which to unify observational constraints. We robustly reevaluate all three of these by (i) simultaneously fitting heat flow, bathymetry, and temperatures derived from a shear velocity model of the upper mantle, (ii) using the three main thermal models (half-space, plate, and Chablis), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 84 publications
(250 reference statements)
0
11
0
Order By: Relevance
“…Subsequently, for ages 147-180 Ma, depth stabilizes at 6700-6760 m (note that the reference depth of 6400 m is exceeded). The semi-empirical depth-age curve computed in this paper may be compared with other curves, produced from various data and based on various assumptions (GOUTORBE and HILLIER 2013). For simplicity, we compare our curve with a selection of others, including those reflecting PSM and GDH1 models as well as the sediment/isostasy-corrected GEBCO with digital isochrons of the oceans proposed by MÜ LLER et al (2008), denoted GEBCO-M. All these use the same depth interval 2500-6400 m. The curve derived in this paper agrees particularly well with fully empirical depth-age relationship from GEBCO-M.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, for ages 147-180 Ma, depth stabilizes at 6700-6760 m (note that the reference depth of 6400 m is exceeded). The semi-empirical depth-age curve computed in this paper may be compared with other curves, produced from various data and based on various assumptions (GOUTORBE and HILLIER 2013). For simplicity, we compare our curve with a selection of others, including those reflecting PSM and GDH1 models as well as the sediment/isostasy-corrected GEBCO with digital isochrons of the oceans proposed by MÜ LLER et al (2008), denoted GEBCO-M. All these use the same depth interval 2500-6400 m. The curve derived in this paper agrees particularly well with fully empirical depth-age relationship from GEBCO-M.…”
Section: Resultsmentioning
confidence: 99%
“…The heat flow decreases with distance from mid-ocean ridges 5 6 7 . Gravity and crustal thickness have been used to constrain thermal contraction models, but the variation of heat flow and see-floor depth with age or distance became the primary constraint on models of the thermal structure and evolution of the oceanic lithosphere 8 9 . Several possible cascade processes have been discussed to interpret the generation and evolution of heat flow, including mantle convection 10 , heat conduction 11 , circulation 12 , heat released during exothermal serpentinisation reactions 13 , heat sources in plumes and magmatic eruptions 14 15 , dike injection 16 and earthquake swarms 17 .…”
mentioning
confidence: 99%
“…These functions fit the observed young age topography and observed old age heat flow well. These three models (PSM, GDH1 and CHABLIS) have been validated by many authors using various types of observed data and they have been often employed as standard models for comparisons 3 8 9 25 26 27 28 29 30 31 32 33 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These temperatures are all potential temperatures. 1994; Hillier and Watts, 2005;Crosby et al, 2006;Zhong et al, 2007;Goutorbe and Hillier, 2013;Hasterok, 2013). The plate model can easily explain the fl attening behavior because the thickness of an aging lithosphere converges to a prescribed value imposed by the bottom boundary condition, typically set at the depth of ~100 km.…”
Section: Comments On Previous Studiesmentioning
confidence: 99%